2020
DOI: 10.5578/mb.69786
|View full text |Cite
|
Sign up to set email alerts
|

İki Anti-HIV Doğrulama Testinin Karşılaştırılması: Rekombinant HIV 1/2 “Line İmmunoassay” ve Geenius HIV 1/2 Doğrulama Testi

Abstract: İnsan immün yetmezlik virüsü (HIV) enfeksiyonu tanısında temel amaç, hızlı ve doğru bir şekilde HIV enfeksiyonuna sahip kişilerin saptanmasıdır. Uluslararası ve ulusal rehberlerin klasik algoritmalarında tekrarlayan şekilde reaktif bulunan örneklerin doğrulanması/desteklenmesi gerektiği önerilmektedir. Uzun yıllardan beri kullanılan rekombinant "line immünoassay testi (LIA)", maliyet ve emek etkin olması için biriktirilerek çalışılmaktadır. Bu çalışmada, rutin tanıda uzun süredir kullandığımız rekombinan HIV 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Among all HIV positive ( n = 229) patients, 1.6% were reactive with 141 (62.1%) confirmed. The increasing ratio of S/CO to 4 automatically increases PPV without uncertainty in sensitivity [ 38 ].…”
Section: Fifth-generation Hiv Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all HIV positive ( n = 229) patients, 1.6% were reactive with 141 (62.1%) confirmed. The increasing ratio of S/CO to 4 automatically increases PPV without uncertainty in sensitivity [ 38 ].…”
Section: Fifth-generation Hiv Testsmentioning
confidence: 99%
“…Similarly, Geenius semi-automated and differentiation assay for HIV-1 and HIV-2 is a rapid assay approved (FDA) and can only be used as supplemental technique in the fourth-generation algorithm, but not as a screening test. It has been reported that Geenius has 100% sensitivity and 96% specificity [ 38 ]. Presently, there is a combo of fourth- and fifth-generation rapid assays which is used for the detection of HIV antigen and antibodies but does not distinguish between antibodies of HIV-1 and HIV-2.…”
Section: Rapid Hiv Assaysmentioning
confidence: 99%